Critical analysis of videolaparoscopic adrenalectomy: the experience of INCA and literature review - Nunes, Luiz Fernando (2003)
In the past, adrenalectomy was performed through open surgery. In 1992, Gagner et al. reported the first laparoscopic adrenalectomy. Since then, many comparative studies have demonstrated the advantages of the laparoscopic approach when compared to traditional open approaches to adrenalectomy. Between May 1995 and May 2002, we performed 16 laparoscopic adrenalectomies. The most frequent disease was adenoma (7), pheochromocytoma (4), metastasis of " non-oat" cell lung cancer (3), hypercortisolism (1), hyperaldosteronism (1). Average tumor size was 3.56 cm (2.0 - 5.5 cm). Eleven patients were females and 4, males, 8 right, 6 left and 1 bilateral glands were removed. Mean age was 50.3 years (30 - 73 years). Average lenght of hospitalization in post-operative period was 2.1 days (1 - 6 days). No mortality ocurred and blood transfusion was not necessary. In one case, the laparoscopic procedure was converted to open surgery after removal of tumor, for hemostatic review. Average operative time was not measured, because the surgery team was different for each adrenalectomies. This manuscript shows our initial experience with laparoscopic adrenalectomy, describe the techinique, reviews the literature and discusses the real advantages of this method: effectiveness and safety with reduced time hospital discharge, related to a less invasive surgery.